PENGARUH KOMUNIKASI ANTAR BUDAYA DALAM KELUARGA KAWIN CAMPUR TERHADAP POLA MENDIDIK ANAK DI KOMPLEK SETIA BUDI INDAH - Rehia K.I.Barus Irfan Simatupang Friska Rizki Noviyanti (Universitas Medan Area, 2016)
Mix marriage as regulated in Article 57 Law Number 1 of 1974 concerning marriage that is committed by a couple with different nationality. The Nationality of the Republic of Indonesia in Law Number 12 of 2006, is explained that children as the result of mix marriage can have double nationalities but limited. The process of communication that is using in the mixing marriage is the process of intercultural communication. In establishment of an interpersonal communication between eastern culture and western culture. This communication takes place not just for a day or two, but takes place during the stay of foreign citizens and citizens relations with in Indonesia. The patterns of children's education is one of the problems that often occur in mixed marriages. Most of the mixing marriage used the foreign pattern of their child's education. This is because foreigners want their children get an education equivalent to the education of the country of origin may be obtained. The results showed that the process of intercultural communication can be well-established and effective among the four mixed marriage couples. Overall informants seeks to honor and respect for cultural differences in their marriage.They tried to blend and merge with the cultur of their partner.Changes in view of the world (religion,values,and behaviors) on minorities and chose to follow the beliefs of the dominant partner.